(untitled) (Eurasian Journal of Philology Science and Education, 2015)
In branch of morphology of language there is a combination concept of structure izafet.This concept was created from the arabic language which designates "Al - from the word idafatu" if to make a straight line it translates gives value as a dopolnitelneniye. Sense izafet type ІІ it is known to us since turkey eras iznacheny udelnost share on neskolky groups. In it article is told opinion about known professor Talgat Sayranbayev about izafet and three types izafet on activity in the offer. And also think of scientists who conveniently I increased izafet. To the second look Izafeta on and combinations, a combination making ditch of words discipline, doesn’t increase the word between words. This izafet long ago belong on a number of combinations. Because this sample meet on written monuments of Turkish peoples and on present turkish languages.